Effects of insomnia symptoms and objective short sleep duration on memory performance in youths. (12th May 2020) - Ling, Jiefan; Sun, Wanqi; Chan, Ngan Yin; Zhang, Jihui; Lam, Siu Ping; Li, Albert Martin; Chan, Joey Wing Yan; Kyle, Simon D.; Li, Shirley Xin
Summary: Sleep quantity and quality are both important for optimal development and functioning during youth. Yet few studies have examined the effects of insomnia symptoms and objective short sleep duration on memory performance among adolescents and young adults. One‐hundred and ninety participants (female: 61.6%) aged from 12 to 24 years completed this study. All participants underwent a clinical interview, a 7‐day actigraphic assessment, a battery of self‐report questionnaires and cognitive tests to assess working memory and episodic memory. Insomnia symptoms were defined as a score ≥ 9 on the Insomnia Severity Index, and objective short sleep duration was defined as average total sleep time less than 7 hr for those aged 12–17 years, and 6 hr for those aged 18 years and above as assessed by actigraphy. Insomnia symptoms were significantly associated with worse self‐perceived memory ( p  < .05) and poorer performance on the digit span task ( p  < .01), but not the dual N‐back task and verbal learning task. There was no significant difference in any of the memory measures between participants with objective short sleep duration and their counterparts. No interaction effect was found between insomnia and short sleep duration on any of the objective memory outcomes. Insomnia symptoms, but not objective short sleep duration, were associated with poorer subjective memory and objective working memory performance in youths. Further studies are needed to investigate the underlying mechanisms linking insomnia and memory impairments, and to delineate the long‐term impacts of insomnia on other aspects of neurocognitive functioning in youth.